2017
DOI: 10.4103/sjg.sjg_1_17
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices of primary health care physicians toward colorectal cancer screening

Abstract: Background/Aim:Early diagnosis of chronic illnesses and cancers mainly occurs at primary health care centers (PHCs) by primary health care physicians (PHPs). The incidence of colorectal cancer (CRC) in the Kingdom of Saudi Arabia (KSA) is rising and this has been attributed to many factors. The increasing incidence of CRC is compounded by nonadherence to screening recommendations. Therefore, evaluating PHPs knowledge, attitudes, and practices of screening for CRC is clinically important. We aimed to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 13 publications
8
42
1
Order By: Relevance
“…[ 47 ] Several reasons may explain this low uptake of CRC screening, including low awareness of screening existence and personal fears,[ 31 32 ] low physician adherence to recommend CRC screening or low expectation of help. [ 48 49 ] Moreover, there is a lack of national policy. [ 23 ] Nevertheless, 75.3% of them would undergo early screening for colon cancer if their doctor advised them to do so.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] Several reasons may explain this low uptake of CRC screening, including low awareness of screening existence and personal fears,[ 31 32 ] low physician adherence to recommend CRC screening or low expectation of help. [ 48 49 ] Moreover, there is a lack of national policy. [ 23 ] Nevertheless, 75.3% of them would undergo early screening for colon cancer if their doctor advised them to do so.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge, behavior, and beliefs of the public are expected to predict the response to a national CRC screening program. A few attempts of identifying the obstacles and challenges in establishing a CRC screening program in Saudi Arabia have been made,[38] but most of these were limited to a number of cities,[1115] while some targeted healthcare professionals[13] or undergraduate students in universities[12] which might not necessarily reflect the target population. It has been demonstrated that the targeted population's perceived severity and susceptibility to CRC and knowledge of guidelines increased the odds of screening intention,[39] thus it would be pertinent to examine acceptance of the public to undergo CRC screening and to explore potential barriers.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Although there is no validated translated version into Arabic, it was converted into an Arabic version and reviewed by two bilingual epidemiologists and a gastroenterologist and used in the original Arabic study that was used in Riyadh[11] and has been reproduced in other publications. [1213]…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 3 ] Despite this scenario, institution of CRC screening and early diagnosis remains a formidable challenge. [ 4 5 6 ] As a consequence, up to 24% of these patients have advanced disease with distant metastasis at initial diagnosis. [ 2 ] The disconnect between the magnitude of the problem and the necessary national action plan is obvious.…”
mentioning
confidence: 99%